2006
DOI: 10.1002/adma.200501765
|View full text |Cite
|
Sign up to set email alerts
|

Rigid, Self‐Assembled Hydrogel Composed of a Modified Aromatic Dipeptide

Abstract: A simple dipeptide self‐assembles into a biocompatible hydrogel (see figure and inside cover). This novel biomaterial is extremely simple to prepare and has a remarkable rigidity. It is very stable under extreme conditions, can be injected, and can be shaped according to the vessel it has been assembled in. The hydrogel allows a wide variety of possible biomedical applications including tissue engineering, axonal regeneration, and controlled drug release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

32
778
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 760 publications
(812 citation statements)
references
References 51 publications
32
778
0
2
Order By: Relevance
“…Again, for related gelators, we have shown that the choice of organic solvent in which the gelator is initially dissolved affects the outcome, 77 which is unsurprising as the solubility of the gelator will be different in each solvent, and different mixing rates of the solvents with water among other variables. Elsewhere, it has been stated that fresh solutions of the gelator in an organic solvent are always prepared to ensure complete dissolution of the LMWG, 73 but this is never actually proven as far as we can see. Mixing of DMSO and water is an exothermic process, which leads to the mixture heating slightly.…”
Section: Process Of Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Again, for related gelators, we have shown that the choice of organic solvent in which the gelator is initially dissolved affects the outcome, 77 which is unsurprising as the solubility of the gelator will be different in each solvent, and different mixing rates of the solvents with water among other variables. Elsewhere, it has been stated that fresh solutions of the gelator in an organic solvent are always prepared to ensure complete dissolution of the LMWG, 73 but this is never actually proven as far as we can see. Mixing of DMSO and water is an exothermic process, which leads to the mixture heating slightly.…”
Section: Process Of Assemblymentioning
confidence: 99%
“…Gels form down to a concentration as low as 1 mg/mL, with more turbid gels forming at 10 mg/mL (the highest concentration tested). As for other related gelators, 73 this method of self-assembly proceeds by the addition of water immediately resulting in a highly turbid solution. This clarifies over a period of minutes as the gel forms.…”
Section: Process Of Assemblymentioning
confidence: 99%
“…According to earlier experimental and theoretical studies these mechanical properties are related to their molecular structure [10,12]. The exceptional mechanical properties of amyloids make them good candidates for a wide range of potential technological applications, and specifically as new bionanomaterials utilizing them as nanowires [13][14][15][16], gels [17][18][19][20][21], scaffolds and biotemplates [13,[22][23][24][25][26][27], liquid crystals [28], adhesives [29] and biofilm materials [30]. These applications often imply the functionalization of the amyloid fibrils with the introduction of additional elements, including enzymes, metal ions, fluorophores, biotin or cytochromes.…”
mentioning
confidence: 99%
“…1,2 A recent expansion in the number of LMWG systems reported has led to a rapid growth in reports of characterisation and applications of a particular class of this type of molecule, namely aromatic conjugated dipeptide LMWG. [3][4][5][6][7][8] These systems typically consist of a hydrophobic, often aromatic, dipeptide sequences conjugated to Fmoc (9-fluorenylmethoxycarbonyl) 9,10 or naphthalene 3,4 ; further conjugations have also been reported. 11,12 Through the use of an environmental cue, 13 such as an enzymatic trigger, 14 temperature, 15,16 or light 12 some of these conjugates selfassemble into anisotropic fibrils that can eventually cause hydrogelation through the immobilisation of water by the fibrillar network.…”
Section: Introductionmentioning
confidence: 99%